Miniaturized microvalve for microfluidics application - Lee, Sheung Jien (2016)
Advances in the field of microfluidics have led to the widespread adoption of microfluidic devices used in a wide range of applications including clinical diagnosis and biochemical research. A main advantage of microfluidic devices such as Micro Total Analysis Systems (μTAS) is that they allow for point-of-care or on-site use, thus significantly reducing analysis times and operating costs. These microfluidic platforms require microfluidic components such as microvalves, which need to be small and easily integrated into existing platforms. This project involves the design, fabrication and characterization of a miniaturized active multi-way microvalve. The microvalve is designed for integration into microfluidic chips and is small in size, reducing the overall size of microfluidic platforms. The microvalve uses a rotary mechanism with a specially designed compressible rotor made of Viton© elastomer to both provide a seal and switch between outlets precisely, with other components made of machined polymethyl methacrylate (PMMA). The microvalve is actuated manually but can be modified to accept automatic actuation using a suitable small stepper motor. The small size, simple design and relative ease of fabrication makes the microvalve presented in this project viable for use in disposable or single-use microfluidic chips which are to be mass manufactured. The miniaturized rotary microvalve presented here in this project is able to withstand pressures up to 370kPa with no leakage and has a switching torque of under 0.03Nm.